Lean Production: A Way To Reduce The Internal Inventory And Cycle Time - Mas'udin, Ilyas (Department Industrial Engineering, University of Muhammadiyah Malang, 2007)
The progressive competition among industries and the increase of customer expectation will lead the progressive efforts in reducing the cost of production and logistic activities in the future. The companies (mass production, job shop and service industries) are forced to tighten their production process effectively by cutting the unnecessary activities in logistic flow, delete dummy and redundant elements, specializing the core business, and eliminate the wastes to simple and make their production process is more competitive. The lean concept could be the alternative way to reduce the main wastes: inventories and production cycle time. Eventhough it is very expensive to implement the lean production in the shop floor production, but the waste elimination and continuous improvement as the main key of the lean thinking has promised a significant improvement and profit for companies which implement the concept. The tools that could be used as methods to make the production process leaner such as just in time with kanban card system, kitting principle, collaborative scheduling and production plan, group technology, cell manufacture design and line balancing are well implemented in the worldwide. The efforts in leaning production will continue due to the lean thinking basically try to make the system better and believe that there is no best system but there is always better system.Â